Research on professional responsibility and ethics in accounting. Vol. 18 - Jeffrey, Cynthia (Emerald, 2014)
Research on professional responsibility and ethics in accounting publishes high-quality research and cases which focus on the professional responsibilities of accountants and how they deal with the ethical issues they face. Covering timely issues such as social responsibility and ethical judgement, the series brings together a range of articles exploring the professional responsibilities of accountants, codes of conduct which affect them, and securities regulations. Compliance with professional guidelines is judgement-based and the characteristics of the individual, the culture in which they operate, and situations all affect how these guidelines are interpreted and applied, as well as when they might be violated. This volume researches the nature of the interactions between accountants, regulators and standard setters, the dilemmas that occur and investigate how and why accountants resolve them.
Keywords: Business & Economics -- Accounting -- General.; Accounting.; Finance & accounting.; Accounting -- Moral and ethical aspects.; Accountants -- Professional ethics.; Business ethics.; elektronické knihy; electronic books